Expansion of India’s national child healthcare programme, Rashtriya Bal Swasthya Karyakram (RBSK), for rare disease management : a health policy perspective - Pragya Chaube; Arun K. Singh; Mohua Chakraborty Choudhury (Orphanet Journal of Rare Diseases, 2023)
Abstract Rare diseases (RD) are severe and debilitating conditions. They are one of the leading causes of childhood mortality globally. In India, RDs have not been considered in most healthcare programs which usually cater to more common diseases. We believe, that for efficient utilization of resources in a resource-constrained healthcare system, existing programs must integrate RD management strategies. In this study, we explore the utility, expandability, and limitation of one of the important national child healthcare programs, Rashtriya Bal Swasthya Karyakram (RBSK) which translates to National Child Healthcare Program. We found that RBSK has immense potential to cater to RDs through some of its unique features, such as comprehensive screening, wide target age group, and efficient utilization of resources. We provide recommendations that can help to strengthen the present program. This study will inspire other low-resource countries to identify and expand existing public healthcare programs for RD management. Moreover, RBSK can serve as a model program to integrate RD management globally.